Unshackling a White Elephant : Disassembling a redundant, monofunctional artefact and reassembling it as a series of regenerative urban green infrastructure interventions that creates resilient multifunctional civil infrastructure - Davey, Calayde Aenis (University of Pretoria, 2023)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2022.